Peningkatan Hasil Belajar Biologi Peserta didik Pada Materi Sistem Saraf Melalui Penggunaan Media Pembelajaran Prezi Desktop Kelas XI IPA SMA Negeri 3 Makassar - Jamaluddin Jamaluddin; Mardiana Suyuti; Edy Wardoyo; Sahrul Sahrul; Ifa Safira (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2021)
This research was a classroom action research that aims to increase the result of students’ Biology study through the use of Prezi Desktop learning. The subject of this research was students of XI IPA SMA Negeri 3 Makassar, in even semester, in academic year 2018/2019. They were 29 students. This research was accomplished into 2 cycles. The data collected was analyzed by using quantitative descriptive analysis. The result of data analysis as belows: (1) The result of students’ biology study by looking at average value after using Prezi Desktop learning media. It increased from 68.23 in the 1st cycle to be 81,50 in the 2nd cycle, the percentage of thorough students was 37.71% in the 1st cycle to be 83.95% in the 2nd Cycle. (2) After using Prezi Desktop media, attitude of the students towards the media was 100% positive. It can be concluded that there was increasing during learning process after applying the use of Prezi Desktop leraning media, and the students also supported 100% towards Prezi Desktop media in learning process at SMA Negeri 3 Makasar.